Fishing for ALK with immunohistochemistry may predict response to crizotinib. Issue 5 (September 2013) - Bavieri, Mario; Tiseo, Marcello; Lantuejoul, Sylvie; McLeer-Florin, Anne; Lasagni, Anna; Fantini, Riccardo; Rossi, Giulio
Background: ALK (anaplastic lymphoma kinase) gene rearrangement is a novel oncogenic driver in non-small cell lung cancer (NSCLC) against which a selective inhibitor, namely crizotinib, is effective. Fluorescence in situ hybridization (FISH) is considered the reference method in selecting patients with ALK-positive tumors for treatment with crizotinib. Case report: We report the case of a 42-year-old non-smoking woman with an advanced pulmonary ALK FISH-negative adenocarcinoma characterized by strong immunohistochemical expression of ALK fusion protein. The patient received targeted therapy with crizotinib in compassionate use and experienced a long-lasting clinical response. Conclusion: FISH testing should not be considered the only method to select patients for therapy with ALK inhibitors and the use of multiple ALK-detecting techniques could be helpful in screening ALK-positive patients more appropriately.